A Theological Reflection on Torture and Democracy - Denton-Borhaug, Kelly (Dialog, 2008)
First, I summarize the major findings of a new comprehensive resource, Torture and Democracy, by Darius Rejali, as corrective for the current state of confusion and concealment in United States with regard to the persistence of torture. Second, I respond theologically to the insights from this scholarship through a) reflection on victims of torture as ‘nonpersons’ in light of theological anthropology, and through exploring the role of Christians in the public square, and b) addressing the problem of sacrificialism.